cDC1 Dependent Accumulation of Memory T Cells Is Required for Chronic Autoimmune Inflammation in Murine Testis - Jing, Yuchao; Cao, Min; Zhang, Bei; Long, Xuehui; Wang, Xiaoming (Frontiers in Immunology, 2021)
As an immune privilege site, there are various of immune cells in the testis. Previous research has been focused on the testicular macrophages, much less is known about the T cells in testis. Here, we found that T cells with memory phenotypes were the most abundant leucocyte in the testis except for macrophages. Our results shown that the proportion of testicular T cells increases gradually from birth to adulthood in mice, and that the primary type of T cells changed from γδTCR+ T cells to αβTCR+ T cells. In addition, under homeostatic conditions, CD8+ T cells are the dominant subgroup, and has different phenotypic characteristics from CD4+ T cells. We found that cDC1, but not cDC2, is necessary for the presence of T cells in the testis under physiological state. Significant decrease of T cells does not have a deleterious effect on the development of the testis or spermatogenesis. However, cDC1 dependent T cells play an indispensable role in chronic autoimmune orchitis of the testis. Collectively, our multifaceted data provides a comprehensive picture of the accumulation, localization and function of testicular T cells.